PERANCANGAN LOGO DAN MEDIA PROMOSI ALASKA MOBIL SEBAGAI UPAYA MENINGKATKAN BRAND AWARENESS - Ariyanto, Agus (Jurnal Art Nouveau, 2014)
Abstract: CV.ALASKA JAYA known as Car Alaska, is a company engaged in trading second car in the city of Surabaya. Not all companies second car providers with innovative and creative concepts, especially in the promotion to the wider community. So, not many people recognize excellence services Car Alaska. The purpose of this design is to know how to design a logo and media campaign as an effort to increase brand awareness. The design uses qualitative methods with the method, observation, in-depth interviews, and existing studies to find a formulation of the concept design. From the analysis of the data found superiority and uniqueness of Alaska Cars that are not conveyed to the public. Promotional activities that have not been done and corporate identity is not known to be a reason why excellence Car Alaska unknown audience. After processing the data analysis found the design concept key words "Smart Choice", which means someone who has the decision, intelligence, selective, and easy to adjust. Which "Smart Choice" explains what to expect and it takes a smart and selective customers, paced lifestyle effective, efficient, and reliable. Audiences are given a fantastic visual display, imaginative thinking, and wonderful things using active and aggressive communication. So the result is expected to increase customer awareness of the brand and company Car Alaska. Â Keywords: Design, Logo, Promotion, Brand Awareness, Second Car, Smart Choice